Analisis SWOT Strategi Kompetitif Dalam Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Kabupaten Manggarai Barat Oleh Badan Pendapatan Daerah - Yohanes Fantriyono Men; Dea Arme Tiara Harahap (JURNAL AKADEMISI VOKASI, 2023)
This research aims to analyze the Strengths, Weaknesses, Opportunities, and Threats of the Regional Revenue Agency's strategy to increase the collection of Rural and Urban Land and Building Tax. This study uses a qualitative descriptive analysis method. The results of the study show that the strength of the Regional Revenue Agency (BAPENDA) is greater than the weakness. Where the highest strengths are employee integrity and the strength of the Regional Revenue Agency (BAPENDA), the highest weaknesses are facilities supporting the main tasks and functions of each inter-sector coordination, digital literacy within the scope of the Regional Revenue Agency's (BAPENDA) strengths, policies to support optimizing the realization of Land Tax and Rural and Urban Buildings (PBB P2) and Administrative composition and completeness of the Regional Revenue Agency (BAPENDA). Externally, the study results show that the opportunities from the strengths of the Regional Revenue Agency (BAPENDA) are greater than the threats. The highest opportunity is increasing investment in West Manggarai Regency which has an impact on economic growth and expansion of the internet network throughout West Manggarai. While the highest threat is the knowledge and understanding of taxpayers about tax digitalization.